An Analysis of the Themes of Refuting Rumors on China's Sina Weibo During the Period of Covid-19 - Difan Guo (Jurnal Audiens, 2021)
From the end of 2019 to 2020, there were countless rumors on the Internet related to COVID-19 during the viral epidemic. This study analyzed how government Weibo, the official news release channel of government social media, refuted rumors on China's leading social media platform Sina Weibo during the COVID-19 pandemic outbreak in China. This study used the LDA topic model to model the Weibo text topic and obtain the topics of the rumors that the government Weibo defied. This study find that the five main topics of rumors presented in the anti-rumor Weibo are highly related to the operation of the social system, disease prevention and treatment, and social security.